Antibacterial Activity Test of Gel Toothpaste from Cinnamon Leaf Essential Oil ( Cinnamomum burmanni Blume.) Against Staphylococcus aureus Bacteria - Putri, Chintya Dwiyunia; Elisma, Elisma; Maharini, Indri (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Cinnamon leaf essential oil can inhibit the growth of Staphylococcus aureus bacteria because it contains cinnamaldehyde and eugenol compounds, which function as antibacterials. Staphylococcus aureus is a bacteria involved in various infections in the mouth and human body. This research aims to formulate cinnamon leaf essential oil into a gel toothpaste preparation by differentiating the concentration of cinnamon leaf essential oil as an active ingredient and testing its antibacterial activity against Staphylococcus aureus bacteria. The concentration of active ingredients in formula I is 0.5%, in formula II, 1%, and in formula III, 1.5%. Evaluation of the physical properties of gel toothpaste preparations includes organoleptic, homogeneity, spreadability, pH, viscosity, foam ability, stickiness, and antibacterial activity test against S. aureus using the well diffusion method. The results of the organoleptic and homogeneity evaluations were analyzed descriptively. In contrast, the spreadability, pH, viscosity, foam height, adhesion, stability, and antibacterial activity tests were analyzedstatistically using One-way ANOVA. Organoleptic test results showed yellowish white (FI), light yellow (FII), and yellow (FIII); all three formulas had a characteristic smell of essential oils and were semisolidand homogeneous. The spreadability test results ranged from 5-5.90 cm, pH value from 5.05-5.47, viscosity value from 31,980-43,900 Cp, foam ability from 9-14 mm and adhesion value from 05.84-08.83 seconds. The antibacterial activity test results for formulas I and II formed an inhibition zone in the strong category, while formula III formed an inhibition zone in the powerful category.